2021
DOI: 10.3389/fped.2021.772800
|View full text |Cite
|
Sign up to set email alerts
|

Case Report and Review of the Literature: Congenital Diaphragmatic Hernia and Craniosynostosis, a Coincidence or Common Cause?

Abstract: Congenital diaphragmatic hernia (CDH) is a life-threatening birth defect that presents as either an isolated diaphragm defect or as part of a complex disorder with a wide array of anomalies (complex CDH). Some patients with complex CDH display distinct craniofacial anomalies such as craniofrontonasal dysplasia or craniosynostosis, defined by the premature closure of cranial sutures. Using clinical whole exome sequencing (WES), we found a BCL11B missense variant in a patient with a left-sided congenital diaphra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…In this study, we reviewed the clinical phenotype of the reported patients with craniosynostosis and BCL11B variants ( 9 , 24 ) and our patient (Table1). One de novo missense variant (c.7C > A, p. Arg3Ser) with craniosynostosis in BCL11B gene has been reported ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we reviewed the clinical phenotype of the reported patients with craniosynostosis and BCL11B variants ( 9 , 24 ) and our patient (Table1). One de novo missense variant (c.7C > A, p. Arg3Ser) with craniosynostosis in BCL11B gene has been reported ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, the boy was otherwise healthy. Recently, another literature has reported four BCL11B missense mutations (p.Gly667Glu, p.Gly582Ser, p.Pro673Arg, p.Pro422Leu) with craniosynostosis or combined congenital diaphragmatic hernia (CDH) and craniosynostosis ( 24 ). All the BCL11B variants were inherited from their normal parents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Craniosynostosis is a disorder of skull formation caused by premature ossification of cranial sutures, occurring in ~1 in 2250 births 6 . Although the first two reports of BCL11B alterations showed no findings of craniosynostosis, five patients have been reported to show craniosynostosis in association with BCL11B alterations, suggesting a relatively less common manifestation in humans 6,11 .…”
mentioning
confidence: 89%
“…The identified variant has not been reported previously and is not registered in any database. The clinical information of this patient is summarized in Table 1 together with previous reports 2,3,[6][7][8][9][10][11][12][13][14][15] .…”
mentioning
confidence: 99%